Determinants of quality of life and well-being in cognitively unimpaired older adults: a systematic review - María Dolores Frías-Luque; Abel Toledano-González (PeerJ, 2022)
Objective It is important to know the psychological variables that are related to quality of life and well-being in healthy elderly people. The main objective of the present review is to analyse which factors, through psychological variables, are determinant on the adaptive processes that acquire relevance in the last stage of life. Data sources An electronic search was conducted in WOS, Science Direct, PsycARTICLES, Psychology Database and Psycinfo. Study selection The search terms used were derived from the combination of the following search string: ((“Emotional Factors” OR “Emotional Effects”) AND (“Emotional Intelligence” OR “Emotional Regulation”) AND (“Quality of Life” OR “Personal Satisfaction”) AND (“Healthy Old People” OR “Healthy Old Adults”) AND (“Healthy Aging” OR “Successful Aging”)). Data extraction 11th April 2021. Data synthesis In total, 13 articles were selected. Conclusions The articles showed the importance of social support, proactive coping strategies (emotional regulation) and emotional intelligence as key factors in the elderly population for their positive influence on variables such as quality of life and well-being. Prospero ID: CRD42021224789